Direct Lytic Agents: Novel, Rapidly Acting Potential Antimicrobial Treatment Modalities for Systemic Use in the Era of Rising Antibiotic Resistance - Schuch, Raymond; Cassino, Cara; Vila-Farres, Xavier (Frontiers in Microbiology, 2022)
Direct lytic agents (DLAs) are novel antimicrobial compounds with unique mechanisms of action based on rapid cell wall destabilization and bacteriolysis. DLAs include two classes of purified polypeptides—lysins (peptidoglycan hydrolase enzymes) and amurins (outer membrane targeting peptides). Their intended use is to kill bacteria in a manner that is complimentary to and synergistic with traditional antibiotics without selection for DLA resistance. Lysins were originally described as having activity against Gram-positive pathogens and of those, exebacase, is the first to have advanced into Phase 3 of clinical development. Recently, both engineered and native DLAs have now been described with potent bactericidal activity against a range of Gram-negative pathogens, including multidrug-resistant (MDR) and extensively drug-resistant (XDR) Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii. Importantly, novel DLAs targeting Gram-negatives, including the lysin CF-370 and the amurin peptides, are active in biological matrices (blood/serum) and, as such, offer promise for therapeutic use as systemically administered agents for the treatment of life-threatening invasive infections. In this review, DLAs are discussed as potential new classes of antimicrobial biologics that can be used to treat serious systemic infections.